ANALISIS PENINGKATAN PERCERAIAN DI WILAYAH HUKUM PENGADILAN AGAMA KELAS 1A KOTA TERNATE - La Tua, Jumaidin; Sahman Nasim, Abu; Marwa, Marwa (Indonesian Journal of Shariah and Justice, 2023)
The phenomenon of increasing divorce in the Class 1 A Religious Court of Ternate is important to discuss. The data shows that in 2016-2020 the Ternate Religious Court decided divorce cases were contested (a divorce application filed by a wife) always dominated divorce divorce cases (a divorce application was filed by a husband). This research is a qualitative research by taking statistical data from the Religious Courts and interviews with perpetrators as well as Judges and Registrars. The results of the study found that the phenomenon of increasing divorce in the Religious Courts had become commonplace. The phenomena of disputes and fights, drunkenness, adultery, domestic violence, polygamy and an uncertain economy have graced the results of judges' decisions in trials, including the Ternate Religious Court. The judge's efforts to carry out mediation efforts have been made but still the increase in divorce continues to occur.